A Band-Aid fix to a problem that's going to be persistent": The influence of social place attachment on rural residents' perceptions of natural hazard relief efforts. (January 2022) - Davis, Cassandra R.; Griffard, Megan Rauch; Burton, Amy; Weinberg, Jacob; Kaneria, Krupa; Smith, Mia; Sabin, Greg; Barnes, Travis
Abstract: Residents in rural communities are more likely to face greater impacts from natural hazards and will likely be burdened by a slower recovery process compared to their non-rural peers. As the number of hurricanes are expected to increase along with catastrophic impacts from climate change, policies are needed to remedy and improve relief efforts of natural hazards, specifically those located in rural, low-income communities. This paper presents a critical review of how rural residents perceive relief efforts from local and federal organizations inside and outside of their communities. The research team conducted 20 structured interviews with individuals heavily impacted by Hurricanes Matthew (2016) and Florence (2018) across four counties in Eastern North Carolina to gauge their level of satisfaction with organizational support. Our findings suggest that residents who have a stronger social place attachment to their community are more likely to look favorably on local non-governmental organizations (NGOs) as compared to federal agencies and national organizations. Emergent policy implications show that local and national organizations would benefit from building relationships with rural residents to assist with reducing communication barriers, especially following a natural hazard.